Drying Kinetics, Physicochemical Properties and Sensory Quality of the Instant Foxtail Millet as Affected by Drying Methods - Yingqiang Wang; Hongxia Zhao; Xi Song; Wenjie Zhang; Feng Yang (Polish Journal of Food and Nutrition Sciences)
The instant foxtail millet was prepared using microwave vacuum drying (MVD), microwave-hot air drying (MHAD), hot air drying (HAD) and traditional roasting (TR). Their effects on drying kinetics, physicochemical properties as well as sensory quality were evaluated and compared. Results showed that the total drying time varied with the drying method used and was about 160, 100, 260, and 45 min for MVD, MHAD, HAD and TR, respectively. The effective moisture diffusion coefficients (Deff) were 6.57×10 -9 m 2 /s, 9.80×10 -9 m 2 /s, 4.14×10 -9 m 2 /s and 6.20×10 -9 m 2 /s for MVD, MHAD, HAD and TR, respectively. Drying resulted in a significant decrease in L* and an increase in a* and b* of the color of products. MVD, MHAD and HAD products had a comparable rehydration ratio and cooking time. Scanning electron microscopy and rehydration process revealed that MHAD and MVD samples had a similar structure with the HAD sample. Drying caused a loss of 6.5–54.9% in the total phenolic content and a loss of 38.4–62.2% in total yellow pigment content. MVD millet displayed the highest total phenolic content (142.56 mg GAE/100 g dry matter) and yellow pigment content (9.56 mg CE/kg dry matter). In sensory evaluation, MHAD, HAD and MVD samples had comparable scores and were all accepted by the panelists, either in dry or rehydrated form. MHAD and MVD can be used as an alternative to hot air drying or traditional roasting in the production of the instant millet due to shorter drying time and better product quality.